How many replicates to accurately estimate fish biodiversity using environmental DNA on coral reefs?. Issue 21 (6th October 2021) - Stauffer, Salomé; Jucker, Meret; Keggin, Thomas; Marques, Virginie; Andrello, Marco; Bessudo, Sandra; Cheutin, Marie‐Charlotte; Borrero‐Pérez, Giomar Helena; Richards, Eilísh; Dejean, Tony; Hocdé, Régis; Juhel, Jean‐Baptiste; et al.
Abstract: Quantifying fish species diversity in rich tropical marine environments remains challenging. Environmental DNA (eDNA) metabarcoding is a promising tool to face this challenge through the filtering, amplification, and sequencing of DNA traces from water samples. However, because eDNA concentration is low in marine environments, the reliability of eDNA to detect species diversity can be limited. Using an eDNA metabarcoding approach to identify fish Molecular Taxonomic Units (MOTUs) with a single 12S marker, we aimed to assess how the number of sampling replicates and filtered water volume affect biodiversity estimates. We used a paired sampling design of 30 L per replicate on 68 reef transects from 8 sites in 3 tropical regions. We quantified local and regional sampling variability by comparing MOTU richness, compositional turnover, and compositional nestedness. We found strong turnover of MOTUs between replicated pairs of samples undertaken in the same location, time, and conditions. Paired samples contained non‐overlapping assemblages rather than subsets of one another. As a result, non‐saturated localized diversity accumulation curves suggest that even 6 replicates (180 L) in the same location can underestimate local diversity (for an area <1 km). However, sampling regional diversity using 25 replicates in variable locations (often covering 10 s of km) often saturated biodiversity accumulation curves. Our results demonstrate variability of diversity estimates possibly arising from heterogeneous distribution of eDNA in seawater, highly skewed frequencies of eDNA traces per MOTU, in addition to variability in eDNA processing. This high compositional variability has consequences for using eDNA to monitor temporal and spatial biodiversity changes in local assemblages. Avoiding false‐negative detections in future biomonitoring efforts requires increasing replicates or sampled water volume to better inform management of marine biodiversity using eDNA. Abstract : Biodiversity estimates from eDNA metabarcoding often uncover only a portion of the diversity in a location. We discover that for species‐rich areas, such as coral reefs, we may need more samples than previously thought to recover and monitor biodiversity in a local area.